The significance of the principle supplet Ecclesia. From the can. 209 of the 1917 Code of Canon Law to the can. 144 of the current Code - interpretation and application” - DOHNALIK, JAN (Prawo Kanoniczne, 2018)
The article is divided into three parts. In the first one works on the formulation of the norm on jurisdiction supply by the Church during the first codification have been reviewed. The author quotes archival documents and preparatory schemata in which one can notice the evolution of what is to become the canon 209. The scope of application of the rule supplet Ecclesia as well as the conditions in which doubt or common error may occur have been specified in the light of authentic interpretations and the canonical heritage of the first half of the 20th century. In the second part the process of creation of the current canon 144 and its interpretation has been outlined. Discussion of these issues during preparation of the new codification and subsequent drafts are quoted after the periodical Communicationes. The meaning of particular elements of the traditional rule’s new formulation is presented in the perspective of former and current commentaries. The third part is dedicated to the application of the supplet Ecclesia principle in the specific situations of the Church’s life. The first paragraph of the canon can be applied among the others in case of invalid acquisition of an ecclesiastical office for undisclosed reasons as well as the death of the ordinary if it remains unknown to the public. The reader will also find discussions about the implementation of the rule in question in connection with canon 883, the circumstances in which the Church supplies the faculty to celebrate the sacrament of penance or the scope of application of the canon 144 in the assistance at marriages. The present elaborate shows that the outline of the history of the interpretation of the supplet Ecclesia principle in the last 100 years helps to better understand and apply the canon 144 of the current Code.